2007
DOI: 10.5194/acp-7-5489-2007
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of ground-based ozone and NO<sub>2</sub> measurements during the MANTRA 2004 campaign

Abstract: In support of the main balloon launch, a suite of five zenith-sky and direct-Sun-viewing UV-visible ground-based spectrometers was deployed, primarily measuring ozone and NO 2 total columns. Three Fourier transform spectrometers (FTSs) that were part of the balloon payload also performed ground-based measurements of several species, including ozone. Ground-based measurements of ozone and NO 2 differential slant column densities from the zenith-viewing UV-visible instruments are presented herein. They are found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The mean relative difference for GBS minus SAOZ ozone is −3.2 ± 0.3 % (see third section of Table 3). This is well within the combined error of the two instruments and is comparable to the values of −6.9 % to −2.3 % found by Fraser et al (2008Fraser et al ( , 2009Fraser et al ( ) for 2005Fraser et al ( -2007, when SAOZ and GBS data were retrieved by the same analysis group, using the same analysis software. This demonstrates that, even when implemented independently with slight differences in the analysis settings and software, the new NDACC data standards are sufficient to produce a homogeneous ozone dataset.…”
Section: Comparisons With Ndacc Doas Measurementssupporting
confidence: 62%
See 1 more Smart Citation
“…The mean relative difference for GBS minus SAOZ ozone is −3.2 ± 0.3 % (see third section of Table 3). This is well within the combined error of the two instruments and is comparable to the values of −6.9 % to −2.3 % found by Fraser et al (2008Fraser et al ( , 2009Fraser et al ( ) for 2005Fraser et al ( -2007, when SAOZ and GBS data were retrieved by the same analysis group, using the same analysis software. This demonstrates that, even when implemented independently with slight differences in the analysis settings and software, the new NDACC data standards are sufficient to produce a homogeneous ozone dataset.…”
Section: Comparisons With Ndacc Doas Measurementssupporting
confidence: 62%
“…Furthermore, the UT-GBS and SAOZ both met NDACC standards during the 2009 Cabauw Intercomparison of Nitrogen Dioxide measuring Instruments (Roscoe et al, 2010). GBS and SAOZ ozone and NO 2 measurements have been compared during several Arctic and mid-latitude campaigns using the same analysis settings and the same software (Fraser et al, 2007(Fraser et al, , 2009.…”
Section: Doas Measurementsmentioning
confidence: 99%
“…7 has been deployed since 2010 for year-round sunlit measurements. SAOZ and UT-GBS TCO data have been compared during several mid-latitude and Arctic campaigns (Adams et al, 2012;Fraser et al, 2007Fraser et al, , 2008Fraser et al, , 2009Roscoe et al, 2010).…”
Section: Saozmentioning
confidence: 99%
“…Many studies have compared WMO-GAW Dobson or Brewer TCO (hereafter referred to as DB TCO) with NDACC UV-visible zenith-sky TCO (referred to as ZS TCO) (Fraser et al, 2007;Hendrick et al, 2011;Høiskar et al, 1997;Kyrö, 1993;Roscoe et al, 1994Roscoe et al, , 2001Van Roozendael et al, 1998;Vaughan et al, 1997). In general, it has been found that ZS TCO retrievals have advantages, such as weak temperature dependence of ozone cross sections (in the visible band), the ability to measure at large SZAs (e.g., during polar sunrise and sunset), and limited sensitivity to clouds compared to DB TCO (Daumont et al, 1992;Hendrick et al, 2011;Scarnato et al, 2009;Van Roozendael and Hendrick, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the UT-GBS and SAOZ both met NDACC standards during the 2009 Cabauw Intercomparison of Nitrogen Dioxide measuring Instruments (Roscoe et al, 2010). GBS and SAOZ ozone and NO 2 measurements have been compared during several Arctic and mid-latitude campaigns using the same analysis settings and the same software (Fraser et al, 2007(Fraser et al, , 2008(Fraser et al, , 2009.…”
Section: Doas Measurementsmentioning
confidence: 99%